Digital Competence and Sustainable Development of Museums: A Literature Review - Yue, Man; Md.Johar, Md.Gapar Bin; Ramly, Rusyda Binti (Journal of Artificial Intelligence and Information, 2025)
This systematic review investigates how digital capabilities influence sustainability in museums, drawing on 273 articles from Web of Science (2000-2024). The findings highlight that digital tools boost economic efficiency, minimize environmental impact, and enrich social engagement. Critical mechanisms driving these outcomes include managerial innovations and resource integration, underpinned by theories such as firm capability, resource-based view, and organizational innovation. Despite these insights, research gaps remain, particularly regarding smaller, county-level museums, long-term sustainability effects, and visitor experiences. The review underscores the importance of strategic digital adoption, especially for resource-limited institutions, to enhance sustainability across economic, environmental, and social dimensions. It recommends that future studies prioritize these underexplored areas to deepen understanding and support the museum sector’s evolution.